2011
DOI: 10.1111/j.1442-9071.2010.02473.x
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole versus natamycin as primary treatment in fungal corneal ulcers

Abstract: Topical 1% voriconazole was found to be safe and effective drug in primary management of fungal keratitis, its efficacy matching conventional natamycin. There was no added advantage of using topical 1% voriconazole over topical natamycin as primary treatment in fungal keratitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 29 publications
(29 reference statements)
1
50
0
3
Order By: Relevance
“…[21][22][23][24][25][26] The relatively common failure of medical therapy is attributed to both poor penetration and variable efficacy of available antifungal medications. [27][28][29][30][31] Therapeutic keratoplasty (TKP) is often required for medically uncontrolled fungal keratitis with or without corneal perforation. [32][33][34][35][36][37][38][39][40][41][42] Although there is a guarded prognosis for the maintenance of graft clarity, [32][33][34][35][36][37][38][39][40][41][42][43][44] subsequent visual rehabilitation with optical keratoplasty (OKP) procedures, [32][33][34][35][36][37][38][39][40][41][42][43][44]…”
mentioning
confidence: 99%
“…[21][22][23][24][25][26] The relatively common failure of medical therapy is attributed to both poor penetration and variable efficacy of available antifungal medications. [27][28][29][30][31] Therapeutic keratoplasty (TKP) is often required for medically uncontrolled fungal keratitis with or without corneal perforation. [32][33][34][35][36][37][38][39][40][41][42] Although there is a guarded prognosis for the maintenance of graft clarity, [32][33][34][35][36][37][38][39][40][41][42][43][44] subsequent visual rehabilitation with optical keratoplasty (OKP) procedures, [32][33][34][35][36][37][38][39][40][41][42][43][44]…”
mentioning
confidence: 99%
“…In vitro studies suggest that susceptibility is drug/species specific. Voriconazole had the broadest spectrum in general, but natamycin had the lowest and better susceptibility for Fusarium species [92,96,97].…”
Section: Azolesmentioning
confidence: 99%
“…Bunya et al [9] reported that voriconazole has been successful when amphotericin B or fluconazole have been unsuccessful in cases of drug-resistant fungal keratitis and endophthalmitis. Arora et al [10] evaluated the efficacy of topical 1% voriconazole versus 5% natamycin in treatment of 30 patients with fungal corneal ulcers. They concluded that topical 1% voriconazole was a safe and effective drug in primary management of fungal keratitis.…”
Section: Discussionmentioning
confidence: 99%